2002
DOI: 10.1039/b205575a
|View full text |Cite
|
Sign up to set email alerts
|

Fine structural photoluminescence spectra of silica-supported zirconium oxide and its photoactivity in direct methane conversion

Abstract: Highly dispersed zirconium oxide species on silica exhibit fine structure in phosphorescence emission spectra showing the vibration energy of the photoactive Zr-O-Si linkage to be 955 cm-1, and the species promotes the photoinduced non-oxidative methane coupling at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Also on silica-supported zirconium oxide evacuated at high temperature, the direct methane coupling proceeds upon photoirradiation [23,24]. The sample of low Zr content less than 0.1 mol% was active for this reaction, suggesting highly dispersed Zr oxide species are the photoactive sites.…”
Section: Silica-based Photocatalysts For Direct Methane Couplingmentioning
confidence: 96%
“…Also on silica-supported zirconium oxide evacuated at high temperature, the direct methane coupling proceeds upon photoirradiation [23,24]. The sample of low Zr content less than 0.1 mol% was active for this reaction, suggesting highly dispersed Zr oxide species are the photoactive sites.…”
Section: Silica-based Photocatalysts For Direct Methane Couplingmentioning
confidence: 96%
“…13 and the photometathesis of propene. 13,14 Additionally, silica-based photocatalysts, such as silica-alumina, 15,16 silica-supported zirconia, 7,17 silica-supported magnesia, 8 and silica-alumina-titania, 9,18 exhibit activity under UV irradiation at room temperature. The photoactive sites were formed on the surface of silica (SiO 2 ) prepared by a sol-gel method.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested the efficient separation of photoinduced electrons and holes by Pt nanoparticles. In the case of Cu 0.1 /PC‐50, a photoluminescence spectrum with fine structure was shown, which could be attributed to the highly dispersed copper species . According to the UV/Vis DRS result, it was suggested that the photoexcitation occurred by charge transfer from oxygen to copper in the clusters.…”
Section: Figurementioning
confidence: 98%